Review of the Technical, Toxicological, and PKPD Considerations for Conducting Inhalation Toxicity Studies on Biologic Pharmaceuticals—The Outcome of a Cross-Industry Working Group Survey. (February 2021) - Wolfreys, Alison; Kilgour, Jo; Allen, Andrew D.; Dudal, Sherri; Freke, Mark; Jones, David; Karantabias, George; Krantz, Carsten; Moore, Simon; Mukaratirwa, Sidney; Price, Mark; Tepper, Jeffrey; et al.
The inhaled route is still a relatively novel route for delivering biologics and poses additional challenges to those encountered with inhaled small molecules, further complicating the design and interpretation of toxicology studies. A working group formed to summarize the current knowledge of inhaled biologics across industry and to analyze data collated from an anonymized cross-industry survey comprising 12 inhaled biologic case studies (18 individual inhalation toxicity studies on monoclonal antibodies, fragment antibodies, domain antibodies, oligonucleotides, and proteins/peptides). The output of this working group provides valuable insights into the issues faced when conducting toxicology studies with inhaled biologics, including common technical considerations on aerosol generation, use of young and sexually mature nonhuman primates, pharmacokinetic/pharmacodynamic modeling, exposure and immunogenicity assessment, maximum dose setting, and no observed adverse effect levels determination. Although the current data set is too small to allow firm conclusions, testing of novel biologics remains an active area and is likely to remain so for molecules where delivery via the inhaled route is beneficial. In the future, it is hoped others will continue to share their experiences and build on the conclusions of this review to further improve our understanding of these complex issues and, ultimately, facilitate the safe introduction of inhaled biologics into clinical use.